Bibliography management with Library Master Version 2.0. - Delozier EP (Medical Reference Services Quarterly, 1994)
Library Master, a bibliographic and textual database management software package, is reviewed in this article. One of over fifty software packages intended to organize and track bibliographies and references, it provides a wide range of data manipulation capabilities. Some of the common capabilities supported include flexible inputting, editing, and deleting of references; sophisticated database querying capabilities; and flexible organization and output of bibliography lists. This review concentrates on the bibliography management capabilities of Version 2.0 from Balboa Software.